Analisis Kuantitatif dan Kualitatif Dokumen Rekam Medis Pasien Bersalin di Klinik Pratama Aisyiyah Siti Khotijah Salam Magelang - Eniyati, Eniyati; KP, Zakharias; Yulaikhah, Lily; Prahesti, Ratna (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: The implementation of health services cannot be carried out properly without good medical record documentation as well. The medical record unit is one of the units that plays an important role from registration to recording the patient's disease history. Medical records are the most important aspect in the hospital management process in medical services. Quality assurance is an effort to periodically review various conditions that affect services, monitor services, and trace the output produced, so that various deficiencies and causes of deficiencies can be known and improvement efforts can be made to further improve the level of health and welfare. Quantitative and qualitative analysis is part of this effort. Purpose: quantitatively and qualitatively analyze medical record documents of maternity patients at the Aisyiyah Siti Khatijah Salam Magelang primary clinic. Result: Based on the results of quantitative observation/analysis, the average total completeness of maternity patient medical records was 93.01%, and did not meet the standards that should be 100%, the Delinguent Medical Record (DMR) had the highest incompleteness, which was in January 2021 at 50%. there were no incompleteness (0%) in April, May and September 2021. The results of the qualitative analysis are completeness of 90%. Conclusion: The average completeness in the medical record of maternity patients is 93.01%, and has not met the standard that should be 100%, the Delinguent Medical Record (DMR) has the highest incompleteness, which is in January 2021 at 50%. The results of the qualitative analysis are completeness of 90%.